Integrative guidance and counseling as a school-based system for preventing adolescent sexual violence: A systematic literature review - Saputri , Riskia Artikalani; Defriyanto, Defriyanto (Universitas Islam Negeri Raden Intan Lampung, 2026)
Sexual violence in adolescents is a complex problem that requires a systematic and integrated prevention strategy in the school environment. This research aims to synthesize how Guidance and Counseling services can be conceptualized as a system for preventing sexual violence in adolescents. The study used a Systematic Literature Review (SLR) design with reporting referring to PRISMA on articles identified through the Scopus database. The core empirical synthesis is based on 16 primary studies, while conceptual sources are used in a limited way to support the theoretical framework. The results of the synthesis identified five main domains, namely school-based interventions, Comprehensive Sexuality Education, social norm change and bystander strengthening, inclusive approaches for vulnerable groups, and risk screening and cross-agency collaboration. Key supporting factors include attitude, self-efficacy, social support, school climate, and safe access to services. The most consistent evidence was found on improved knowledge, attitudes, awareness, and self-efficacy, while evidence of long-term behavior change was limited. This study proposes an integrative Guidance and Counseling model as a school-based prevention system that connects primary, secondary, and tertiary prevention and provides a conceptual basis for the development of sexual violence prevention services in schools.